Food-based approaches to combat the double burden among the poor : challenges in the Asian context. - Khor, Geok Lin (Wiley-Blackwell, 2008)
Estimates of FAO indicate that 14% of the population worldwide or 864 million in 2002-2004 were undernourished in not having enough food to meet basic daily energy needs. Asia has the highest number of undernourished people, with 163 million in East Asia and 300 million in South Asia. Meanwhile obesity and diet-related non-communicable diseases continue to escalate in the region. The double burden of malnutrition also affects the poor, which is a serious problem in Asia, as it has the largest number of poor subsisting on less than $1/day. As poverty in the region is predominantly rural, agriculture-based strategies are important for improving household food security and nutritional status. These measures include shifting toward production of high-value products for boosting income, enhancing agricultural biodiversity, increasing consumption of indigenous food plants and biofortified crops. Urban poor faces additional nutritional problems being more sensitive to rising costs of living, lack of space for home and school gardening, and trade-offs between convenience and affordability versus poor diet quality and risk of contamination. Time constraints faced by working couples in food preparation and child care are also important considerations. Combating the double burden among the poor requires a comprehensive approach including adequate public health services, and access to education and employment skills, besides nutrition interventions.